Effect of Wrapping Papers on Physiological Changes and Shelf-life of Mango cv. Langra - Roy, R; Rahim, MA; Alam, MS (Journal of Environmental Science and Natural Resources, 2012)
Effect of different wrapping postharvest treatments viz. T0 (control treatment), T1 (White paper), T2 (Brown paper), T3 (Tissue paper) and T4 (News paper) on physical changes of mango var. Langra were analyzed. Among, the treatments, the maximum 5.25 days was required for ripening in Langra which was kept in white paper and minimum 3.573 days for ripening was recorded in control fruits of mango. The highest total soluble solid (18.60% Brix) was found at over-ripe in brown paper treated fruits and weight loss (16.07%) was occurred in controlled fruits of Langra whereas and the lowest (7.235 and 2.735%, respectively) was in recorded in tissue paper treated fruit at pre-ripe and 3 days after storage, respectively. The maximum shelf life 11.50 days was observed from the mango variety cv. Langra which was treated in brown paper and minimum 7.833 days was found in controlled fruits of Langra. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10152 J. Environ. Sci. & Natural Resources, 4(2): 99-103, 2011